Postmortem Heart School - Zeybek, Volkan; Kurtuluş, Ayşe; Kara, Cüneyt Orhan; Kaftan, Asuman; Kılıç, İsmail Doğu and Ersoy, Gökhan and Acar, Kemalettin (The Bulletin of Legal Medicine, 2019)
Introduction: Autopsy is the first and only choice in determining cause of death in sudden cardiac death. An updated guideline has been published by the AssociationforEuropean Cardiovascular Pathology for describing sudden death/ sudden cardiac death, autopsy procedure and laboratory tests to be performed. The aim of this study is to evaluate postmortem cardiac school program, which is planned based on this guideline. Material Method: Course program has theoretical and practical training. A 10-question test was developed for the participants in accordance with their learning objectives to be used at the beginning and end of course. Experiences of trainees were evaluated by South East Thames short interactive course evaluation scale. Two items were added to learn the thoughts of participants on the skills acquisition. A section was formed in which trainees could write their thoughts about course in order to be used in qualitative evaluation. Results:The pre-test and post-test averages of participants were compared, there was statistically significant increase compared to pre-training. The results of course evaluation scale are examined; it was understood that the majority of participants were satisfied with education process and they felt sufficient in terms of ability to dissection of heart after training. Discussion:Postmortem Heart School education applied to forensic medicine students has a positive effect on knowledge and skill levels of sudden cardiac death and heart dissection in short term. It is planned to evaluate the long-term effects of this training together with the number of participants in addition to other courses.